2020
DOI: 10.1155/2020/5373927
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Outcome of Gynecologic Laparoendoscopic Single‐Site Surgery with a Homemade Device and Conventional Laparoscopic Instruments in a Chinese Teaching Hospital

Abstract: Objective. To demonstrate various benign gynecologic diseases that can be performed by laparoendoscopic single-site surgery (LESS) with conventional laparoscopic instruments. Method. Patients with benign gynecologic diseases that need ovarian cystectomy, fallopian tube resection, or myomectomy were divided into experimental group and control group, and perioperative outcomes of these patients were analyzed. Results. From November 2017 to May 2018, 65 LESS gynecological surgeries were performed, among which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Recurrence after surgery or drug therapy is a major characteristic of ovarian endometrioid cysts. In view of the minimally invasive and aesthetically pleasing nature of the laparoscopy, laparoscopy is currently the first choice for the treatment of ovarian endometrioid cysts and is suitable for the removal of cysts in the vast majority of patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence after surgery or drug therapy is a major characteristic of ovarian endometrioid cysts. In view of the minimally invasive and aesthetically pleasing nature of the laparoscopy, laparoscopy is currently the first choice for the treatment of ovarian endometrioid cysts and is suitable for the removal of cysts in the vast majority of patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%